Peran Kepala Sekolah Sebagai Pemimpin Pembelajaran Dalam Membangun Sekolah Berkualitas Berdasarkan Teori Weber’s 1996 - yogi wiratomo; Muhyidin, Mohammad; Karim, Abdul; Japar, Muhammad; Herdiati, Dian (LEADERIA: Jurnal Manajemen Pendidikan Islam, 2024)
This article examines the role of principals as instructional leaders based on Weber's theory (1996), which emphasizes five main dimensions in instructional leadership: school mission, curriculum and instruction management, learning climate, support for professional development, and monitoring and evaluation of learning. The study uses a qualitative approach and literature review to identify concrete steps that principals can take to build a quality educational environment that is responsive to the needs of students and the community. The findings indicate that implementing these five dimensions plays a crucial role in improving student learning outcomes and teaching effectiveness in schools. Principals who can effectively manage pedagogical, managerial, and social competencies can create a conducive learning climate and foster collaboration. This article recommends that principals strengthen their data analysis skills, encourage continuous professional development, and involve the entire school community in data-driven decision-making to achieve more optimal educational goals.